Pembelajaran daring materi mengurutkan gambar menjadi cerita pada siswa kelas II SDN 189 Neglasari menggunakan model picture and picture - Darmayanti, Tina; Fauzi, Muhammad Rizal; Septiyan Rahayu, Galih Dani (IKIP Siliwangi, 2025)
This study aims to examine the learning material of sorting pictures into stories for Class II students using an online-based Picture and Picture model. The research method used is descriptive qualitative. The subjects in this study were Class II students of SDN 189 Neglasari Bandung City with a total of 20 students. The instruments used were teacher and student observation sheets, test questions, and teacher and student interview questionnaires. The results showed that there was an increase in the quality of learning when the Picture and Picture model was applied. This is indicated by the average value of understanding the Indonesian language class of 82.00 which belongs to the good category, the highest score of students is 100 and the lowest value is 60. Student learning completeness shows 90.0% of students get scores above the minimum completeness criteria and 10 .0% still got a score below the minimum completeness criteria value.